Relationship among Organizational Justice, Work Engagement and Positive Organizational Behavior of Nurses via Mediation of their Personal Career Goals - M Keyvanar; S Shahpouri; HR Oreyzi (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Each group of staff has their individual career goals in work place. The aim of the study was to determinate mediational role of personal career goals attainment in relation to organizational justice, work engagement and positive organizational behavior.   Material & Methods: It was a correlational study. The statistical population was all female nurses working in Isfahan Alzahra hospital in 2013. Among them 208 nurses were recruited by stratified proportion to size random sampling method. The research instruments were organizational justice inventory (Niehoff & Moorman, 1993), Utrecht Work Engagement scale (2002), a researcher made personal career goals attainment tool and positive organizational behavior (Nguyen & Nguyen 2011). The direct and indirect effects were examined using Normal distribution test and Bootstrap procedure in Preacher and Hayes (2004) SPSS Macro program (2004).   Results: The findings indicated direct and indirect effects of career goals attainment in relation to organizational justice, work engagement and positive organizational behavior (P < 0.05). Conclusion: The results have significant implications for managers of hospitals toward establishing organizational justice and consequently, creating career engagement and positive organizational behavior among the nurses. The organizational justice is related to positive organizational behavior (hope, optimism, self-efficacy, and resiliency) and work engagement through the personal career goals attainment. Therefore, hospital managers can benefit from all profits of positive organizational behavior and work engagement.